2009 Picture Coding Symposium 2009
DOI: 10.1109/pcs.2009.5167472
|View full text |Cite
|
Sign up to set email alerts
|

Coding techniques in Multiview Video Coding and Joint Multiview Video Model

Abstract: During the standardization of MVC, there was also a project namely Joint Multiview Video Model (JMVM), which focused on the advanced coding tools that are potentially useful. Those coding tools adopted into JMVM, including illumination compensation and motion skip, have not been added into MVC specification. In this paper, coding techniques in MVC as well as the tools in JMVM are described and discussed, focusing on the coding efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…While the first version of HEVC standard provides temporal scalability, the SHVC provides spatial, signal-to-noise ratio, bit depth, and color gamut scalability functionalities, as well as various combinations of any of these [28] [49]. The SHVC test model (SHM 10) document and the latest reference software (SHM 12) can be found in [50] and [51], respectively. The common conditions under which the performance of SHVC is tested can be found in [52].…”
Section: E Scalable Extension Hevc (Shvc)mentioning
confidence: 99%
“…While the first version of HEVC standard provides temporal scalability, the SHVC provides spatial, signal-to-noise ratio, bit depth, and color gamut scalability functionalities, as well as various combinations of any of these [28] [49]. The SHVC test model (SHM 10) document and the latest reference software (SHM 12) can be found in [50] and [51], respectively. The common conditions under which the performance of SHVC is tested can be found in [52].…”
Section: E Scalable Extension Hevc (Shvc)mentioning
confidence: 99%
“…If the coding mode for coding MB is intra mode, using the model defined by (6) to estimate its transmission distortion, else, using the model defined by (7) to estimate its transmission distortion, this distortion plus the quantization distortion is the end to end distortion. Using the end to end distortion, bit rate for this mode, as well as the 2 λ defined by J M λ .…”
Section: Joint Source-channel Rdo For Mode Selection Algorithmmentioning
confidence: 99%
“…Among these schemes, "Hierarchical B Pictures [5] " proposed by HHI has been selected by MPEG as reference scheme for its excellent performance [6] . It has been confirmed that the coding gain main come from the hierarchical B frames in temporal direction in [5], furthermore, the inter view prediction will increase much computational complexity in MVC.…”
Section: Introductionmentioning
confidence: 99%
“…It features tools such as hierarchical Bpictures [15], context adaptive binary arithmetic coding (CABAC), and disparity compensation [16,17]. The last one is the novel tool introduced in MVC in order to provide better inter-view prediction.…”
Section: State Of the Art In Multi-view Video Codingmentioning
confidence: 99%